An efficient mesh updating technique for fluid-structure interaction problems - Mouroutis, Z.S.; Markou, George; Papadrakakis, Manolis; Charmpis, Dimos C. (My University, 2007)
The purpose of this paper is to present a robust mesh updating technique combined with an efficient solution algorithm applicable to large-scale fluid-structure interaction problems. We show that a combination of the dimensional torsional spring concept and a preconditioned conjugated gradient type method, for the solution of the "elasticity" problem, provides a powerful tool for this computationally intensive problem. © 2007 World Scientific Publishing Company.
Keywords: Coupled problems; Solution algorithms; Mesh updating